What childcare engineering can do to support children in medical care - KOTANI, HIROKO (Transactions of Japanese Society for Medical and Biological Engineering, 2021)
In recent years, with the development of neonatal care, the number of children who require medical care even after discharge from the NICU has been increasing, and the number is estimated to be about 20,000 nationwide. The number of non-medical personnel who operate medical equipment is expected to increase due to the expansion of the system for accepting children with medical care in day-care centers. In medical care, correct knowledge and understanding is necessary because there are cases where procedures differ between infants and adults, and if procedures are not performed correctly, they may not only be ineffective but may also worsen the medical condition. In addition to training for non-medical personnel, standardization of the user interface of pediatric medical devices is expected from the viewpoint of accident prevention.We would like to think about what childcare engineering can do to support children with medical care.